Surgical Management of Massive Labial Edema in a Gravid Preeclamptic Diabetic - Jennifer S. Lindsey; James E. DeVente (Hindawi Limited, 2014)
Background. Massive labial edema is a rare complication during pregnancy that can jeopardize vaginal delivery, as well as leading to maternal and fetal morbidity. It can be related to systemic pathologies, but has been commonly associated with preeclampsia and diabetes. This increased and sometimes longstanding pressure may result in a "labial compartment syndrome" leading to microvascular damage and tissue necrosis if not resolved in a timely fashion. Case. Massive labial edema was treated first conservatively and then surgically in a gravid diabetic patient with severe preeclampsia. Immediately after Cesarean section, the labial compartment syndrome was relieved surgically and resolved rapidly. Conclusion. When conservative attempts at management of labial edema fail, or rapid resolution is critical to maternal and fetal outcome, surgical alternatives should be considered.